ANALISIS PENINGKATAN COMPUTATIONAL THINKING MELALUI MEDIA PETA HARTA KARUN UNTUK SISWA SEKOLAH DASAR - Fita Ama, Sentia; Habibah, Siti; Sofwan, Muhammad; Ayuni Esya Putri, Febby (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the improvement of Computational Thinking (CT) skills in elementary school students through the Treasure Map learning media. The low CT ability of elementary school students has become an increasingly urgent issue amid the 21st-century competency demands of the Merdeka Curriculum. The lack of concrete, non-digital CT learning media appropriate for elementary school students' cognitive development represents a research gap that needs to be addressed. This study employs a descriptive qualitative approach with data collection through participatory observation, in-depth interviews, and documentation. Research subjects were teachers and fifth-grade students at SDN 111/I Muara Bulian. The results show that the Treasure Map media effectively improved all four CT components: decomposition, pattern recognition, abstraction, and algorithmic thinking. The media also proved effective in increasing student motivation and enthusiasm through a contextual gamification approach that does not require digital devices.